Correction: A simple and traceless solid phase method simplifies the assembly of large peptides and the access to challenging proteins. Issue 8 (7th July 2017) - Ollivier, N.; Desmet, R.; Drobecq, H.; Blanpain, A.; Boll, E.; Leclercq, B.; Mougel, A.; Vicogne, J.; Melnyk, O.
Abstract : Correction for 'A simple and traceless solid phase method simplifies the assembly of large peptides and the access to challenging proteins' by N. Ollivier et al., Chem. Sci., 2017, DOI: ; Web:10.1039/c7sc01912b .